Combining camera trap surveys and IUCN range maps to improve knowledge of species distributions - Chen, Cheng; Granados, Alys; Brodie, Jedediah F.; Kays, Roland; Davies, T. Jonathan; Liu, Runzhe; Fisher, Jason T.; Ahumada, Jorge; McShea, William; Sheil, Douglas; Mohd-Azlan, Jayasilan; Agwanda, Bernard; et al. (Conservation Biology, 2023)
Reliable maps of species distributions are fundamental for biodiversity research and conservation. The International Union for Conservation of Nature (IUCN) Red List range maps are widely recognized as authoritative representations of species' geographic limits, yet they might not always align with actual occurrence data. Recent Area of Habitat (AOH) maps remove unsuitable habitat from IUCN ranges to reduce commission errors, but remain untested. We tested concordance between occurrences from camera trap surveys and predicted occurrences from IUCN and AOH maps for 510 medium- to large-bodied mammalian species in 80 camera-trap sampling areas. Across all areas, cameras detected only 39% of species expected to occur based on IUCN ranges or AOH maps, with 85% of the “IUCN-only” mismatches occurring within 200 kilometers of range edges. Only 4% of species occurrences were detected by cameras outside of IUCN ranges. The probability of mismatches between cameras and IUCN range was significantly higher for smaller-bodied mammals and habitat specialists in the Neotropics and Indomalaya, and in areas with shorter canopy forests. Our findings suggest that range and AOH maps rarely underrepresent areas where species occur, but may more often over represent ranges by including areas where a species may be absent, particularly at range edges. We suggest that combining range maps with accumulating data from ground-based biodiversity sensors, such as camera traps, provides a richer knowledge base for conservation mapping and planning.
Keywords: Species distributions; Range map; IUCN; Mammal distribution; Camera trap; Mammal occurrence